Mapping the Student Experience: A Framework for Assessing Student Support, Success, Community and Voice - Tom Lowe; Sophie Wright (Student Success, 2024)
A challenge persists in modern higher education regarding gaining an understanding of the activities and services that facilitate student support, student success, student community and student voice. As modern universities continue to grow in both size and complexity, gaining an understanding of the operations for enhancing and supporting both students’ experiences and outcomes grows in importance for resource allocation and supporting student success for university administrators. These exploratory or audit-based activities attempt to gain an understanding of students' engagement, time pressure and, relatedly, their calendar journeys throughout their higher education, with an aim to create coherence as opposed to chaos in students’ journeys. This case study shares a tested practice from a UK higher education institution of a method to map the so-called ‘student experience’ across a whole university. This framework for mapping student engagement activities takes an asset-based approach beginning with the core activities which lead a student to graduation prioritising activities by time of students’ engagement. This framework is inclusive of the core student experience and the optional, complementary extracurricular activities (Student Community), supporting services (Student Support), and enhancement activities engaging students in the development of education (Student Voice) to gain oversight of complex institutions. This case study offers a transferable framework for use in institutions globally with potential to be implemented as a management tool for administrator and faculty member understanding of the student experience with a view to make enhancements to support student success resourcing and interventions.